1996
DOI: 10.1074/jbc.271.7.3581
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Elements That Control Transcription Activation and Unsaturated Fatty Acid-mediated Repression of the Saccharomyces cerevisiae OLE1 Gene

Abstract: In Saccharomyces cerevisiae, unsaturated fatty acids are formed from saturated acyl-CoA precursors by Ole1p, a ⌬-9 fatty acid desaturase. OLE1 mRNA levels are differentially regulated by the addition of saturated or unsaturated fatty acids to the growth medium. One component of this regulation system involves the control of OLE1 transcription. Saturated fatty acids induce a 1.6-fold increase in transcription activity, whereas a large family of unsaturated fatty acids repress OLE1 transcription as much as 60-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 27 publications
6
127
1
Order By: Relevance
“…In S. cerevisiae, a similar pattern of regulation of the OLE1 gene, which encodes the D-9 desaturase, has been reported; the level of OLE1 gene transcription was increased in response to exogenous saturated fatty acids, whereas exposure to unsaturated fatty acids sharply reduced transcription (McDonough et al, 1992). Although the corresponding positive and negative response elements have been characterized in the OLE1 upstream promoter region (Choi et al, 1996;McDonough et al, 1992), preliminary sequence comparison did not reveal the same elements present in the upstream region of the LIP1 gene. The transcription activation and/or repression elements required for fattyacid-mediated LIP1 expression remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, a similar pattern of regulation of the OLE1 gene, which encodes the D-9 desaturase, has been reported; the level of OLE1 gene transcription was increased in response to exogenous saturated fatty acids, whereas exposure to unsaturated fatty acids sharply reduced transcription (McDonough et al, 1992). Although the corresponding positive and negative response elements have been characterized in the OLE1 upstream promoter region (Choi et al, 1996;McDonough et al, 1992), preliminary sequence comparison did not reveal the same elements present in the upstream region of the LIP1 gene. The transcription activation and/or repression elements required for fattyacid-mediated LIP1 expression remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of signals from repeated experiments (data not shown) demonstrated that the level of hypoxic expression of KlOLE1, similar to KlPDC1, was reduced but not abolished in the mutant strain. OLE1 is repressed by UFAs in S. cerevisiae (Choi et al, 1996). We tested the effect of UFAs on the hypoxic induction of KlOLE1.…”
Section: Expression Of Hypoxic Genes In Gdk/klmga2d Strainmentioning
confidence: 99%
“…Also, the acyl-CoA binding protein and the Ssn6-Tup1 complex were shown to be involved in repression of OLE1 (Fujimori et al, 1997). On the other hand, the Hap1 transcriptional activator (Choi et al, 1996) and two transcription factors, Spt23 and Mga2p, which are initially synthesized as inactive ER-bound precursors, positively regulate OLE1 expression (Zhang et al, 1999). Ole1p is a naturally short-lived enzyme and is degraded by ubiquitin/ proteasome-dependent ER-associated degradation (Braun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures and during oxygen limitation, OLE1 expression is induced (Kwast et al, 1998;Nakagawa et al, 2002). A deletion analysis of the OLE1 promoter identified a 111 bp fatty acid-regulated region (FAR) which is essential for transcription activation and repression by unsaturated fatty acids (Choi et al, 1996). In addition, the low oxygen response promoter element (LORE) mediates oxygen repression of OLE1 (Nakagawa et al, 2001;Vasconcelles et al, 2001).…”
Section: Introductionmentioning
confidence: 99%